Competitiveness at work: is it necessary? / Nor Haniza Hasan and Dr. Tuan Sarifah Aini Syed Ahmad - Hasan, Nor Haniza; Syed Ahmad, Tuan Sarifah Aini (UiTM Cawangan Negeri Sembilan, 2022)
Humans are not products of factories. They possess different qualities and standards. However, when work is concerned, there are certain keys of performance index (KPI) that workers need to fulfil in order to maintain productivity and standard of an organization. Besides, KPI is also used to evaluate work performance. Rush (2022) defines KPI as a measurable tool of evaluating how well an organization is performing in pursuing its key business goals. According to Louise (2016), KPI is not only important for measuring the employees’ targets but also it creates a learning atmosphere where learning takes place to improve performance, stimulates employees to receive important information in order to keep up-to-date information, encourages accountability where vital statistics of performance are revealed, and boosts employees’ morale when they receive positive feedback from the superiors.